Ma’anil Hadith Hashah and Gharar on Buying and Selling Darts as a Condition in the Balloon Darts Game - Wardatur Rohmah, Nur Maulidya; Muhid, Muhid (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2024)
This research is motivated by the desire to understand the application of the concepts of hashah and gharar in modern buying and selling transactions, especially in the context of the Balloon Darts game. The main objective of this study is to analyse the suitability of the mechanism of buying and selling darts in the Balloon Darts game with sharia principles. The research method used is a literature study with a qualitative approach, as well as analysis of primary and secondary literature on hadith and scholars' views related to hashah and gharar by approaching the theory of ma`anil hadith. The results showed that the Balloon Darts game mechanism contains elements of uncertainty and speculation that are not in accordance with Islamic economic principles. Based on the analysis, it is recommended to avoid transaction practices that contain uncertainty and pay more attention to clarity and fairness in every economic transaction in accordance with sharia principles.